2000
DOI: 10.1128/iai.68.12.6611-6617.2000
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Surfactant Protein A with Lipopolysaccharide and Regulation of Inflammatory Cytokines in the THP-1 Monocytic Cell Line

Abstract: Pulmonary surfactant protein A (SP-A) is involved in innate immunity in the lung. In this study we investigated the interaction of SP-A with different serotypes of lipopolysaccharide (LPS) on the regulation of inflammatory cytokines in vitro. In the human monocytic cell line, THP-1, combining SP-A with lipid A or rough LPS further enhanced lipid A- or rough LPS-stimulated tumor necrosis factor alpha (TNF-α) mRNA levels, while SP-A-elicited increases in TNF-α mRNA levels were partially neutralized. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 49 publications
(69 reference statements)
2
14
1
Order By: Relevance
“…Similar to pretreatment with LPS, SP-A can induce a state of tolerance to subsequent endotoxin exposures and result in diminished production of TNF-␣ (32). Conversely, in a monocytic cell culture line, SP-A itself was able to induce TNF-␣ expression (32). Our results support the hypothesis that tolerance to repeated doses of endotoxin can develop and that SP-A may play an important role in this process.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Similar to pretreatment with LPS, SP-A can induce a state of tolerance to subsequent endotoxin exposures and result in diminished production of TNF-␣ (32). Conversely, in a monocytic cell culture line, SP-A itself was able to induce TNF-␣ expression (32). Our results support the hypothesis that tolerance to repeated doses of endotoxin can develop and that SP-A may play an important role in this process.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, SP-A has been reported to induce a state of tolerance to endotoxin. Similar to pretreatment with LPS, SP-A can induce a state of tolerance to subsequent endotoxin exposures and result in diminished production of TNF-␣ (32). Conversely, in a monocytic cell culture line, SP-A itself was able to induce TNF-␣ expression (32).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that SP-A enhances TNF-␣ production via the activation of NF-B signaling cascade (41,73). The present findings indicate that O 3 decreases the ability of SP-A to activate the NF-B cell signaling pathway by reducing the levels of the free NF-B subunit p65 available for translocation to the nucleus and initiation of transcription.…”
Section: Discussionsupporting
confidence: 57%
“…Although the identity of the macrophage cell surface receptor that mediates SP-A initiation of NF-B activation has not been determined yet, previous work from our lab and others indicates interaction of SP-A with Tlr-2 (54,79) or Tlr-4 (25). Moreover, our published findings have shown that the downstream effect of this activation may involve translocation of cytoplasmic NF-B into the nucleus, NF-B binding to the specific DNA elements, and subsequent upregulation of TNF-␣ expression (41,73,79).…”
mentioning
confidence: 98%
See 1 more Smart Citation